Characterization of a novel thermostable alkaline lipase derived from a compost metagenomic library and its potential application in the detergent industry - Li, Qing-Qing; Zhu, Zi-Ran; Liu, Qing-Gang; An, Yu-Ting; Wang, Yi-Xiang; Zhang, Shu-Bin; Li, Gang (Frontiers in Microbiology, 2022)
Using composted soil samples, a metagenomic library consisting of 36,000 clones was constructed. Then, a novel lipase, Lip54q, which belongs to the VIII family of lipolytic enzymes, was identified from the metagenomic library by functional screening. To explore the enzymatic properties of Lip54q, lip54q was heterologous expressed in Escherichia coli with a high expression level of recombinant protein up to 720 mg/L. The recombinant enzyme showed the highest activity (28,160 U/mg) against a C10 substrate at pH 9.0 and 47°C, and was stable at temperatures ≤50°C and pH 8.0–11.0. Of particular interest, the surfactants, Tween-20, Tween-80 and Tritonx-100, exhibited strong promoting effects on Lip54q activities regardless of whether low concentrations (0.1%) or high concentrations (10%) were used. Application studies of Lip54q using six commercial detergents indicated that the enzyme had strong tolerance and immersion resistance to all six detergents. The results of oil-stain removal experiments suggested that addition of the enzyme to various commercial detergents could significantly improve the abilities of these detergents to remove oil-stains. Furthermore, the results of a molecular docking analysis of Lip54q showed that both the C10 substrate and linoleic acid molecules could form hydrogen bond interactions with the catalytic amino acids, Ser-268, Glu-168, and Asp-192, in the catalytic center of the enzyme, and the hydrogen bond distances were shorter. The electrostatic attraction between the enzyme and the substrate formed by the hydrogen bond with a shorter distance is stronger, which is conducive to the formation of a more stable complex between the enzyme and the substrate, thus increasing the activity of the enzyme to such substrate. These results 1ay a good foundation for application of this enzyme in the detergent industry in the future.